2004
DOI: 10.1080/02699050410001672350
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of invalid neuropsychological test performance after traumatic brain injury

Abstract: The TOMM and CVLT-II are sensitive to the potential impact of current financial compensation seeking and prior psychiatric history on neuropsychological test performance after TBI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
53
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(59 citation statements)
references
References 43 publications
(39 reference statements)
5
53
0
1
Order By: Relevance
“…Using the original form of the CVLT (Delis et al, 1987), Connor et al (1997) found that a cutoff of less than 14 of 16 correct successfully classified 95% of individuals exhibiting inadequate effort of the total group. In a recent study using the current CVLT-II FCR, Moore and Donders (2004) examined agreement between scores on the FCR and the TOMM. The authors used an a priori cutoff of less than 15 of 16 on the FCR and0or a score of less than 45 on the second trial of the TOMM in a cohort of individuals with varying levels of traumatic brain injury and found 89% agreement between the CVLT-II FCR and TOMM.…”
Section: Introductionmentioning
confidence: 99%
“…Using the original form of the CVLT (Delis et al, 1987), Connor et al (1997) found that a cutoff of less than 14 of 16 correct successfully classified 95% of individuals exhibiting inadequate effort of the total group. In a recent study using the current CVLT-II FCR, Moore and Donders (2004) examined agreement between scores on the FCR and the TOMM. The authors used an a priori cutoff of less than 15 of 16 on the FCR and0or a score of less than 45 on the second trial of the TOMM in a cohort of individuals with varying levels of traumatic brain injury and found 89% agreement between the CVLT-II FCR and TOMM.…”
Section: Introductionmentioning
confidence: 99%
“…Secondary memory and learning ability were evaluated with the third edition of the Wechsler Memory Scale (WMS-III) [49][50][51][52][53], the full version of the second edition of the California Verbal Learning Test (CVLT-II) [54][55][56], and the Rey Complex Figure Test. The likelihood that the responses given on neuropsychological testing were sincere and that the subjects were applying a good effort was assessed by interpretation of performance on several tests, including the Test of Memory Malingering [57][58], the WMS-III [52][53], and the MMPI-II [59]. Depression was assessed with the second edition of the Beck Depression Inventory [60].…”
Section: Neuropsychological Assessmentmentioning
confidence: 99%
“…For example, the Forced Choice trial in the California Verbal Learning Test -II (CVLT-II; Delis & Kramer, 2000) and the Rey-15 (Rey, 1964) have been found to have similar precision and strong agreement with the TOMM (McCaffrey, O'Bryant, Ashendorf, & Fisher, 2003;Moore & Donders, 2004). In a study examining the relationships between malingering tests on the TOMM, the , and the validity tests on the Minnesota Multiphasic Personality Inventory -Second Edition (MMPI-2; Hathaway & McKinley, 1989) it was found that the TOMM and the Rey-15 held a positive significant relationship, while the validity tests on the MMPI-2 did not positively correlate with the TOMM or Rey-15, indicating that the MMPI may be measuring a different construct .…”
Section: Introductionmentioning
confidence: 82%
“…Performance on the instrument is considered not to be impeded by age, gender, education level, depression, anxiety, and pain (Strauss, Sherman, & Spreen, 2006). However, clinicians are cautioned when administering the TOMM to individuals with premorbid psychiatric history, moderate to severe dementia, and financial incentives to malinger (Moore & Donders, 2004). In regard to elderly samples (e.g., cognitively intact, cognitive impairment without dementia, and with dementia), the TOMM has been found to be successful in identifying malingering when dementia has been ruled out (Teichner & Wagner, 2004).…”
Section: Introductionmentioning
confidence: 99%